Ganti Nama di Kalangan Keturunan Tionghoa Peraturan dan Kebebasan - Sutanto, Irzanti (UI Scholars Hub, 2002)
In 1966 New Order regime imposed a regulation that demands Indonesian citizens of Chinese descendants to change their name with